PENGEMBANGAN PRODUK TAHU SEHAT SEBAGAI ALTERNATIF PANGAN BERGIZI DI DESA LAMBUSA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Abdullah, Sukmawati (Universitas Halu Oleo, 2025)
This community service activity aims to increase the use of tofu as a nutritious food through the development of healthy tofu products in Lambusa Village, Konda District, South Konawe Regency. The main problems faced by the community and small businesses in the village are limited knowledge about tofu processing innovations, low product variety, and suboptimal added value. Through training and mentoring programs, this activity introduces more hygienic techniques for making healthy tofu, the use of quality raw materials, and product innovations such as high-protein tofu, vegetable tofu, and tofu-based snacks. The implementation methods included nutrition education, live demonstrations, and production outcome evaluations. The results of the activities showed an improvement in participants' skills in production techniques, product variety, and understanding of the importance of healthy and value-added foods. Thus, the development of this healthy tofu product has the potential to become a nutritious food alternative as well as an opportunity to increase income for the people of Lambusa Village.